4X+3-2X=15-5U-11

Simple and best practice solution for 4X+3-2X=15-5U-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4X+3-2X=15-5U-11 equation:


Simplifying
4X + 3 + -2X = 15 + -5U + -11

Reorder the terms:
3 + 4X + -2X = 15 + -5U + -11

Combine like terms: 4X + -2X = 2X
3 + 2X = 15 + -5U + -11

Reorder the terms:
3 + 2X = 15 + -11 + -5U

Combine like terms: 15 + -11 = 4
3 + 2X = 4 + -5U

Solving
3 + 2X = 4 + -5U

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2X = 4 + -3 + -5U

Combine like terms: 3 + -3 = 0
0 + 2X = 4 + -3 + -5U
2X = 4 + -3 + -5U

Combine like terms: 4 + -3 = 1
2X = 1 + -5U

Divide each side by '2'.
X = 0.5 + -2.5U

Simplifying
X = 0.5 + -2.5U

See similar equations:

| 7x-61=-4x+71 | | 8x-66=-2x+74 | | v^2+v-53=3 | | 5(4x-4)+1=20x-19 | | -23-4x=-9x+56 | | 1-7(-1/-2) | | 2m-9n-5m+4n=0 | | 700=100+4Q | | -43+7x=29+x | | 6-(-54/7) | | 17+b=25 | | 6/7*-9 | | 16+3x= | | -46+5x=-x+56 | | y=16+3x | | 2-30/39 | | 6-(-57/7) | | 68/13-4 | | -59+2x=16-3x | | -5x+1oy=0 | | 10x+18=5x+138 | | 2x^2-12=116 | | 204/39 | | -113+5x=-9x+41 | | 6x-3=16-63 | | 3x-9=-13 | | 8Y-5=4A-3 | | 7(1)+3(2)= | | 9x-40=60+4x | | 12x^2+17x-13=-8 | | 12+32=12x-7 | | 4x+12=30-6x |

Equations solver categories